Creating walkable streets as a liveability indicator to enhance health and well-being: an assessment of Oxford Street in Osu, Accra - Semordzi, Walter (My University, 2021)
Walkable streets as an element of liveability, form part of a growing global aspiration to create liveable cities. Walkable streets serve various activities, facilitate interaction and social cohesion, reduce car usage, encourage frequent walking, and impact health, safety, and security. These principles are attributes of the New Urbanism. This research report sought to assess Osu Oxford Street’s walkability using selected walkable street indicators. The research method adopted was qualitative. Inquiry forms (checklists), secondary data, and literature review were the data collection tools. Findings show that the study area, Osu Oxford Street, located in Accra, Ghana ,lacked some walkability elements and that pedestrians were particularly vulnerable road users due to a lack of pedestrian infrastructure. The study concluded that Osu Oxford street’s walkability could be enhanced with street design guidelines. The research report recommended the need for broad stakeholder consultations to develop walkable streets, especially for existing contexts, to co-produce walkable streets that resonate with the local people and road users
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Urban Studies in the field of Urban Management